Exploring the potential of human urine derivatives in circular agriculture: a case study on lettuce - Nicastro, Rosalinda; El-Nakhel, Christophe; Geelen, Danny; Fusco, Giovanna Marta; De Pascale, Stefania; Rouphael, Youssef; Carillo, Petronia (Frontiers in Sustainable Food Systems, 2024)
Unlocking the potential of sustainable agriculture relies on innovative approaches such as recycling crop waste and exploiting wastewater. Herewith, human urine derivatives were integrated into the fertigation of soilless-grown lettuce. The effects were remarkable: not only did they impact primary metabolites such as amino acids, proteins, and sugars, but they also influenced secondary metabolites such as polyphenols and anthocyanins, along with antioxidant enzyme activity. K-struvite, a urine precipitate with CaO and NaOH, elicited responses comparable to those of the control NPK and correlated with high biometric values. Interestingly, urine precipitate–CaO and electrodialysis (ED) concentrate stimulated accumulation of leaf polyphenols and anthocyanins, while urine precipitate–CaO induced high ABTS antioxidant capacity, highlighting their potential to enhance antioxidant activity and nutritive quality. Moreover, hydrolyzed urine and aurin induced a significant boost of essential amino acid content, underlining their role in increasing the nutritive value of lettuce. However, they also correlated with higher levels of MDA, a marker of lipid peroxidation, and reduced APX activity, indicating the need for further optimization. These findings underscore the promising role of human urine as an organic component in soilless lettuce fertilization, paving the way for more sustainable and resource-efficient agricultural practices.